Effects of combined inoculation of AM Fungi and Azospirillum on the Growth and Yield of Onion (Allium cepa L.) - and K. Ramakrishnan2, S. Sridevi1*, (Journal of Phytology, 2010)
An experiment was conducted to study the effect of AM (Arbuscular mycorrhizae) fungi and Azospirillum on onion (Allium cepa L.). Both the inoculants were applied by seed, seedling and soil application method.Â These inoculants were tried at as a single and dual inoculation and comprised with control.Â Over all influences by these two beneficial microbes played a vital role in supplying N and P to the onion and found enhanced the growth and yield over the untreated control.Â Â Key words: Onion, AM fungi, Azospirillum, Dual inoculation, Biofertilizer <span style="line-height: 110%; font-variant: small-caps; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; mso-fareast-font-family: SimSun; mso-fareast-language: EN-SG; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-SG; mso-bidi-language: AR-SA;" lang="EN-SG">S. Sridevi and K. Ramakrishnan. Effects of combined inoculation of AM Fungi and Azospirillum on the Growth and Yield of Onion (Allium cepa L.). J Phytol 2/1 (2010) 88-90.